A Case of CD5-/Cyclin D1+/SOX11- Mantle Cell Lymphoma with an Aberrant Immunophenotype and Indolent Clinical Course - Zhang, MD, PhD, Lei; Zhang, MD, PhD, Nan; Zhang, MD, PhD, Nan (North American Journal of Medicine and Science, 2017)
Mantle cell lymphoma (MCL) is a clinically aggressive B-cell lymphoma associated with 11q13 translocation, which leads to cyclin D1 overexpression in almost all cases. Although CD5 expression is characteristic in MCL, rare CD5 negative cases with variable expression of CD10 and CD23 have been reported. Over the recent years, a subgroup of MCL with a relatively indolent clinical course started to be recognized. Herein, we report a case of CD5-/Cyclin D1+/SOX11- MCL in a 75-year-old female with diffuse and persistent lymphoma involving multiple lymph nodes, spleen, bone marrow, and lacrimal ducts over the course of nine years. Despite multiple chemotherapy regimens, the MCL had slowly progressed while her baseline health condition remained stable. The neoplastic lymphocytes from different time points during her clinical course showed similar histological features, genetic abnormality, and immunophenotypes. In particular, the lymphoma cells were CD5-, with overexpression of cyclin D1, aberrant expression of CD10 and BCL-6, absence of SOX11 expression, and presence of t(11; 14) (q13; q32) translocation. The indolent clinical course and unusual immunophenotype suggest this particular type of MCL may be considered a unique subentity under MCL. [N A J Med Sci. 2017;10(1):40-44. DOI: 10.7156/najms.2017.1001040]